Europejski podręcznik historii jako próba wypracowania wspólnej pamięci zbiorowej obywateli Unii Europejskiej - Lesiewicz, Elżbieta (Wydawnictwo Naukowe WNPiD UAM, 2012)
The Euro-handbook and common collective memory of Europeans are the two topics of considerations in this paper. As indicated by its title, the author assumes that there is no com- mon collective memory of the residents of Europe and that a common handbook for European history has failed to be written so far. The considerations are divided into two parts. The first focuses on the common collective memory and related issues, the second presents a number of controversies over a common handbook for the history of European Union citizens. The con- cept of a common European memory is relatively new, and since it emerged it has been a pro- ject to be realized, a reality to be created, by making references to various social, cultural, historical, political, moral and economic categories. Memory is one of the most important fac- tors in building community: a familial, linguistic, national, religious and territorial commu- nity. Therefore, the policy of the European Union is to a large extent concentrated on building a ‘collective memory’. This is about the Europeanization of culture and symbolization of pub- lic space which supports a sense of familiarity, and the consciousness that there is a common spiritual and intellectual European heritage. It is, however, difficult to develop a common Eu- ropean memory since that collective memory is divided; it is a conglomerate of different per- spectives and different versions. This obstacle makes it impossible to write a common handbook of European history. The Old Continent can hope for a divided or dialogue mem- ory, that is for an agreed memory that goes beyond a national horizon. Memory understood in this way could become a foundation for a Euro-handbook taking into account various histori- cal experiences and interpretations of events. If such an agreed handbook were written it could play a significant role in shaping the common memory policy. Therefore, there is a need for a wise and modern history handbook, where teaching would serve reconciliation. The out- come of such teaching is to involve tolerance and peaceful coexistence.
The European History Handbook as an Attempt to Develop the Collective Memory of EU Citizens
Keywords: pamięć zbiorowa; historia UE